Islamic Planning Theory - Sitti Fatimah; Muslimin Kara; Rahmawati Muin (Molang: Journal Islamic Education, 2026)
Islamic economic design theory is a conceptual framework that integrates sharia values in all economic activities with the aim of realizing fair, sustainable, and benefit-oriented welfare. This research aims to analyze the basic concepts of Islamic economic design theory, the principles that underlie it, and its implementation in building an economic system that is in accordance with Islamic values. The research uses a qualitative approach with the library research method. Data was obtained from various secondary sources, such as scientific journals, books, regulations, and literature related to Islamic economics, then analyzed using content analysis techniques. The results of the study show that the theory of Islamic economic design is built on the principles of monotheism, caliphate, justice ('adl), balance (tawazun), and benefit (maslahah) which are the basis in the system of production, distribution, consumption, and management of economic resources. In addition, the Islamic economic system rejects the practice of usury, gharar, and maysir, and encourages productive, transparent, and socially responsible economic activities. The implementation of this theory contributes to the creation of a more inclusive economic system, equitable distribution of income, community empowerment, and sustainable development. Thus, Islamic economic design theory offers a paradigm of economic development that is not only oriented towards growth, but also on achieving balanced welfare between material, social, moral, and spiritual aspects in accordance with the goals of Islamic sharia (maqāṣid al-syarī'ah).